2017
DOI: 10.15446/dyna.v84n203.60531
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liquid phase and mechanical properties during osmodehydrofreezing of papaya (carica papaya L.)

Abstract: The aim of this study was to evaluate the influence of osmotic treatments on the freezing rate, drip loss (DL), elastic modulus (EM) and stress of yield limit (σL) of papaya (Carica papaya L.) samples stored under freezing conditions. Dehydration was performed using an osmotic sucrose solution with 55 and 45 ºBrix for 30 and 90 min. Osmotically dehydrated papaya samples were frozen at -40°C and stored for 10, 20, 30 and 60 days. Fresh fruit was used as a control sample during freezing storage. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…As partial removal of water, especially from plant tissues, induces the concentration of cytoplasmatic components, the depression of the freezing point, the increase of supercooling, and microcrystallization, as well as a significantly lower proportion of ice crystals to the unfrozen phase, damage of cellular integrity as well as drip loss, caused by freezing, is expected to be substantially decreased. In [ 101 ], it was found that papaya samples, pretreated with 45 and 55% sucrose for 90 min (at room temperature) exhibited lower drip loss with respect to control samples, when stored at −40 °C for a period of up to 60 days. The beneficial effect of OD pretreatment on thawed broccoli and radish drip loss was also confirmed in [ 66 ] and [ 80 ], respectively, especially when ultrasound was additionally applied.…”
Section: Quality Degradation During Frozen Storage Of Odf Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…As partial removal of water, especially from plant tissues, induces the concentration of cytoplasmatic components, the depression of the freezing point, the increase of supercooling, and microcrystallization, as well as a significantly lower proportion of ice crystals to the unfrozen phase, damage of cellular integrity as well as drip loss, caused by freezing, is expected to be substantially decreased. In [ 101 ], it was found that papaya samples, pretreated with 45 and 55% sucrose for 90 min (at room temperature) exhibited lower drip loss with respect to control samples, when stored at −40 °C for a period of up to 60 days. The beneficial effect of OD pretreatment on thawed broccoli and radish drip loss was also confirmed in [ 66 ] and [ 80 ], respectively, especially when ultrasound was additionally applied.…”
Section: Quality Degradation During Frozen Storage Of Odf Productsmentioning
confidence: 99%
“…As partial removal of water, especially from plant tissues, induces the concentration of cytoplasmatic components, the depression of the freezing point, the increase of supercooling, and microcrystallization, as well as a significantly lower proportion of ice crystals to the unfrozen phase, damage of cellular integrity as well as drip loss, caused by freezing, is expected to be substantially decreased. In [101], it was found that papaya samples, pretreated with 45 and 55% sucrose for 90 min Regarding texture retention during frozen storage, the shelf life study showed that osmodehydrofrozen compared with conventionally frozen sliced cucumbers, strawberries retained their firmness for prolonged storage period [33,60]. In [40], it was demonstrated that, after a year of storage, the firmness of samples pretreated with high dextrose equivalent maltodextrin (HDM), oligofructose, and the mixture of oligofructose/trehalose was about 18-75% higher than the corresponding values of the untreated tomato samples, although, in all cases, texture was observed to rapidly degradate.…”
Section: Drip Lossmentioning
confidence: 99%